2019
DOI: 10.1161/strokeaha.119.027134
|View full text |Cite
|
Sign up to set email alerts
|

Siponimod (BAF-312) Attenuates Perihemorrhagic Edema And Improves Survival in Experimental Intracerebral Hemorrhage

Abstract: Background and Purpose— Perihemorrhagic edema (PHE) is associated with poor outcome after intracerebral hemorrhage (ICH). Infiltration of immune cells is considered a major contributor of PHE. Recent studies suggest that immunomodulation via S1PR (sphingosine-1-phosphate receptor) modulators improve outcome in ICH. Siponimod, a selective modulator of sphingosine 1-phosphate receptors type 1 and type 5, demonstrated an excellent safety profile in a large study of patients with multiple sclerosis. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 39 publications
5
47
1
1
Order By: Relevance
“…Considering the potent cytotoxic and proinflammatory capacity of NK cells, these results suggest that prevention of NK cell infiltration into the brain might be a viable approach to reduce brain inflammation and attenuate PHE formation after ICH. In light of these studies, a randomized, placebo-controlled, subject-and investigator-blinded trial of another S1PR modulator, siponimod, in ICH patients is ongoing (NCT03338998; Bobinger et al, 2019). Although the benefits of S1PR modulation in improving outcome following ICH awaits more clinical evidence, immune modulation targeting lymphocytes to prevent PHE formation and neurological deterioration deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the potent cytotoxic and proinflammatory capacity of NK cells, these results suggest that prevention of NK cell infiltration into the brain might be a viable approach to reduce brain inflammation and attenuate PHE formation after ICH. In light of these studies, a randomized, placebo-controlled, subject-and investigator-blinded trial of another S1PR modulator, siponimod, in ICH patients is ongoing (NCT03338998; Bobinger et al, 2019). Although the benefits of S1PR modulation in improving outcome following ICH awaits more clinical evidence, immune modulation targeting lymphocytes to prevent PHE formation and neurological deterioration deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In our proceeded paper ( https://www.ncbi.nlm.nih.gov/pubmed/31558140 ), we demonstrated that a second-generation selective S1P-receptor modulator, Siponimod, dose-dependently attenuated the development of secondary brain injury in acute stage of ICH, resulting in improved neurological functions of ICH animals in a short-time study [ 13 ]. Furthermore, we demonstrated that in long term, Siponimod increased the survival rate of treated compared to nontreated animals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we demonstrated that in long term, Siponimod increased the survival rate of treated compared to nontreated animals. However, the long-term effects of Siponimod have not been further evaluated yet [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since peripheral immune cells (especially lymphocytes) do not play a role in organotypic slice culture models, this experimental setup has shown convincingly that siponimod can have beneficial effects in the context of MS by directly modulating the brain cell function. Accordingly, the protective effect of siponimod is not only limited to EAE but has also been observed in other models such as intracerebral hemorrhage [125], where it limits the formation of perihemorrhagic edema, and in experimental stroke [126], where it limits peripheral immune cell recruitment, as well as in a mouse model of diffuse large B-cell lymphoma [127].…”
Section: From Fty720 To Siponimodmentioning
confidence: 88%